More answers

Well, isn't that a happy little math problem we have here? To solve 4ab x 2a, you simply multiply the numbers together. First, multiply the numbers: 4 x 2 = 8. Then, multiply the variables: a x a = a^2, and b x nothing is just b. So, the final answer is 8a^2b. Just like painting a beautiful landscape, math can be a lovely and calming experience when you break it down step by step.

Q: What is 4ab x 2a?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

4ab - 2a - 7

4ab * 3a = 12a2b -----------

Write x and y in terms of integers, which we call a and b. For some integer, x = 2a + 1 y = 2b + 1 Multiplying them, you get: xy = (2a+1)(2b+1) = 4ab + 2a + 2b + 1 Since the first terms are even, adding one makes the final result odd.

4a2+4ab+b2 in2

Assuming that non-leading numbers are exponents, the expression becomes12a^2b + 8a - 5a^2b + 2ab - 4ab^2 + 6ab - 2a - 3ab= 7a^2b + 6a + 5ab - 4ab^2= a*(7ab + 6 + 5b - 4b^2)

Related questions

Urmm 4ab ?

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.

2a(2b) Would Give You The Answer 4ab. 2x2 = 4 And a x b = ab.

2a*2b = 4ab

4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]

4ab - 2a - 7

2a(2b-c) :P

4ab * 3a = 12a2b -----------

Considering the minus sign between 5ab and 6b2 then we have the polynomial as 6a2 + 5ab - 6b2. The polynomial is a quadratic polynomial.Steps to factorize a quadratic polynomial:1 - Multiply first term by third term. 6a2 x (-6b2) = -36a2b22 - If possible break the second term into two terms such that they multiple to -36a2b2. If not then it is factorized by Sridharacharya's formula.5ab can be broken as 9ab + (-4ab).These two terms multiply to give -36a2b2.So we can write 6a2 + 5ab - 6b2 = 6a2 + 9ab + (-4ab) - 6b2.6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)(3a - 2b).So the factors are (2a + 3b) and (3a - 2b).

5 = 1 x 5, 21 = 3 x 7 3 x 5 = 15, 1 x 7 = 7, 15 - 7 = 8 so: (5x + 7)(x - 3)

Write x and y in terms of integers, which we call a and b. For some integer, x = 2a + 1 y = 2b + 1 Multiplying them, you get: xy = (2a+1)(2b+1) = 4ab + 2a + 2b + 1 Since the first terms are even, adding one makes the final result odd.

You have to multiply base x height - in this case, you obtain (4a)(2a+b). This can't be simplified; you can leave it as it is (factored), or multiply it out to obtain 8a2 + 4ab.